2019
DOI: 10.1371/journal.pone.0214523
|View full text |Cite
|
Sign up to set email alerts
|

Integration of heterogeneous functional genomics data in gerontology research to find genes and pathway underlying aging across species

Abstract: Understanding the biological mechanisms behind aging, lifespan and healthspan is becoming increasingly important as the proportion of the world's population over the age of 65 grows, along with the cost and complexity of their care. BigData oriented approaches and analysis methods enable current and future bio-gerontologists to synthesize, distill and interpret vast, heterogeneous data from functional genomics studies of aging. GeneWeaver is an analysis system for integration of data that allows investigators … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 54 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…It contains almost 200,000 public gene sets incorporated from databases, including the Kyoto Encyclopedia of Genes and Genomes (KEGG), Molecular Signatures Database (MSigDB), the drug-related gene database of the Neuroscience Information Framework (NIF), and Online Mendelian Inheritance of Man (OMIM), among many others. Types of GeneWeaver Data that are returned when searching for “senescence OR aging OR longevity” include aging-related (1655 datasets), Gene Ontology (GO) term-based (71), Mammalian and Human Phenotype (63 and 109, respectively), Quantitative Trait Loci (409), Medical Subject Headings (231), gene expression (169), and drug-related gene sets (253) [ 34 ]. GeneWeaver is freely accessible and allows for the uploading of one’s own datasets (with the option to make public or private) to facilitate meta-analysis.…”
Section: Databases For Aging Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…It contains almost 200,000 public gene sets incorporated from databases, including the Kyoto Encyclopedia of Genes and Genomes (KEGG), Molecular Signatures Database (MSigDB), the drug-related gene database of the Neuroscience Information Framework (NIF), and Online Mendelian Inheritance of Man (OMIM), among many others. Types of GeneWeaver Data that are returned when searching for “senescence OR aging OR longevity” include aging-related (1655 datasets), Gene Ontology (GO) term-based (71), Mammalian and Human Phenotype (63 and 109, respectively), Quantitative Trait Loci (409), Medical Subject Headings (231), gene expression (169), and drug-related gene sets (253) [ 34 ]. GeneWeaver is freely accessible and allows for the uploading of one’s own datasets (with the option to make public or private) to facilitate meta-analysis.…”
Section: Databases For Aging Researchmentioning
confidence: 99%
“…Among the GeneWeaver tools available for use are the Combine, Jaccard Similarity, GeneSet Graph, STRING, and Ingenuity Pathway Analysis (IGA) tools. A more in-depth application of these tools and of the use of GeneWeaver in aging-related studies can be found in a recent publication [ 34 ]. Briefly, the Combine tool returns a single gene set from multiple input gene sets that counts the number of sets in which each gene is found.…”
Section: Databases For Aging Researchmentioning
confidence: 99%
See 3 more Smart Citations